2006
DOI: 10.1159/000091975
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein Expression in the Epidermis of Wild-Type and COX-2 Transgenic Mice

Abstract: Cyclooxygenases (COX) 1 and 2 are the key enzymes of prostaglandin biosynthesis. Like in many tissues, in adult skin COX-1 is a constitutive ‘housekeeping’ enzyme, while COX-2 is induced transiently in stress situations such as tissue damage and regeneration. In human skin carcinomas and corresponding early-stage cancer lesions, permanent COX-2 expression and activation is a consistent feature. Knockout and various transgenic approaches and pharmacologic studies show strong evidence for a cause-and-effect rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Genetic study of COX-2 knockout mice has revealed a strong correlation between COX-2 expression and cancer development, indicating that COX-2 contributes to carcinogenesis and oncogenesis [42, 43]. Our previous findings also suggest several cancer-related biological effects of COX-2, including anti-apoptotic effect, cell transformation, and cell cycle progression in different context [44].…”
Section: Discussionmentioning
confidence: 83%
“…Genetic study of COX-2 knockout mice has revealed a strong correlation between COX-2 expression and cancer development, indicating that COX-2 contributes to carcinogenesis and oncogenesis [42, 43]. Our previous findings also suggest several cancer-related biological effects of COX-2, including anti-apoptotic effect, cell transformation, and cell cycle progression in different context [44].…”
Section: Discussionmentioning
confidence: 83%
“…Several lines of evidence has accumulated suggesting that inducible form of COX‐2, a central enzyme in the prostaglandin (PG) biosynthetic pathway, plays an important role in tumorigenesis 28. Knockout and various transgenic approaches and pharmacologic studies show strong evidence for a cause‐and‐effect relationship between the aberrant COX‐2 expression and tumor formation in numerous animal models, including in mouse skin 29. In a multistage skin carcinogenesis experiment with a classical initiation/promotion using DMBA and TPA, COX‐2 deficiency led to a gene dosage‐dependent reduction of the papilloma yield and incidence compared with wild‐type mice 30.…”
Section: Discussionmentioning
confidence: 96%
“…COX-2 is known to promote cancer development. Using COX-2 knockout mice, a strong correlation between COX-2 expression and cancer development was revealed, indicating that COX-2 contributes to carcinogenesis and oncogenesis (Muller-Decker et al , 2006). In this study, we report that co-exposure to arsenic and ethanol induces high COX-2 expressions in a variety of colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%